Shape Dependence on the Electrochemistry of Uncoated Magnetite Motifs. Issue 8 (1st August 2022) - Salvatore, Kenna L.; Vila, Mallory N.; McGuire, Scott C.; Hurley, Nathaniel; Huerta, Citlalli Rojas; Takeuchi, Esther S.; Takeuchi, Kenneth J.; Marschilok, Amy C.; Wong, Stanislaus S.
Abstract : Using a variety of synthetic protocols including hydrothermal and microwave-assisted methods, the morphology of as-prepared magnetite has been reliably altered as a means of probing the effect of facet variations upon the resulting electrochemical processes measured. In particular, motifs of magnetite, measuring ∼100 to 200 nm in diameter, were variously prepared in the form of cubes, spheres, octahedra, and plates, thereby affording the opportunity to preferentially expose either (111), (220), or (100) planes, depending on the geometry in question. We deliberately prepared these samples, characterized using XRD and SEM, in the absence of a carbonaceous surfactant to enhance their intrinsic electrochemical function. Herein, we present a direct electrochemical comparison of specifically modified shape morphologies possessing 3 different facets and their impact as electrode materials for Li-ion batteries. Our overall data suggest that the shapes exhibiting the largest deliverable capacities at various current densities incorporated the highest surface energy facets, such as exposed (220) planes in this study. The faceted nature of different morphologies highlighted a trend in electrochemistry of (220) > (111) > (100); moreover, the degree of aggregation and polydispersity in prepared samples were found to play key roles as well.